2014
DOI: 10.1093/annonc/mdu216
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, phase II study of afatinib versus cetuximab in metastatic or recurrent squamous cell carcinoma of the head and neck

Abstract: Afatinib, an oral irreversible ErbB family blocker, showed comparable activity to cetuximab in patients with recurrent/metastatic head and neck squamous cell carcinoma in this phase II trial. Further, sequential EGFR/ErbB treatment provided sustained clinical benefit in some patients, suggesting a lack of cross-resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
119
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(127 citation statements)
references
References 23 publications
4
119
1
3
Order By: Relevance
“…Afatinib activity has been seen in cetuximab refractory patients in clinical trials, suggesting a lack of cross-resistance in some instances (21,41). Similarly, our present study has shown that afatinib is effective for cetuximabresistant cell lines.…”
Section: Discussionsupporting
confidence: 81%
“…Afatinib activity has been seen in cetuximab refractory patients in clinical trials, suggesting a lack of cross-resistance in some instances (21,41). Similarly, our present study has shown that afatinib is effective for cetuximabresistant cell lines.…”
Section: Discussionsupporting
confidence: 81%
“…Other trials can also be interrogated with regard to EGFR inhibitor response and HPV status, even though these results have to be viewed with caution because of the small sample size. In a small cohort of patients treated with afatinib or cetuximab, similar response rates were found [18]. Preliminary results from the PARTNER study also showed responses to panitumumab treatment in p16-positive and -negative tumors [51].…”
Section: Predictive Biomarkersmentioning
confidence: 54%
“…Afatinib also did not improve OS in comparison with methotrexate but conferred a small benefit in terms of progression-free survival (PFS) [17]. In a phase II trial, afatinib showed antitumor activity comparable to cetuximab [18]. …”
Section: Targeted Therapies In Head and Neck Cancermentioning
confidence: 99%
“…There was no statistically significant difference in ORR (2.7%, 7.6%, and 3.9%, respectively) or median OS (5.6, 6.0, and 6.7 months, respectively). A randomized phase II comparison of afatinib 50 mg/day versus standard-dose cetuximab demonstrated a similar DCR (50% vs. 57%), with an increase in grade $3 AEs with afatinib, including diarrhea (15% vs. 0%), rash (18% vs. 8%), and mucositis (12% vs. 0%) [55]. This study's design allowed crossover, and tumor shrinkage was observed in 40% and 31% of patients who crossed over to afatinib or cetuximab, respectively.…”
Section: Chemotherapy In Recurrent or Metastatic Diseasementioning
confidence: 91%